93.4k views
4 votes
Please help me out!​

Please help me out!​-example-1
User James Lim
by
5.1k points

2 Answers

3 votes
Answer: s = -9


Solution:
18-7s=-9s to -7s=-9s-18 (change the sign of the constant [18] and then move it to the right)

Now move the variable (-9s) to the left side and change its sign as well (now it's just +9s)

Now we have -7s + 9s= -18

Combine the like terms (-7s+9s)

Now we have 2s= -18

And then divide both sides of the equation by two (which equals s = -9)

And then you have your answer, s = -9

Hope you have a great day, God bless! :)
User Anupam Yadav
by
5.7k points
1 vote
The answer will be s = -9
User Vicky Gill
by
5.2k points